A new approach: Enhancement of solubility of rofecoxib - Ramana, M V; Himaja, M; Dua, Kamal; Sharma, V K; Pabreja, Kavita (Asian Journal of Pharmaceutics (AJP), 2014)
The present study is aimed at improving the dissolution of poorly soluble drug, rofecoxib. Rofecoxib, being a drug, basic in nature shows a better solubility in acidic environment. Hence, an attempt was made to provide an acidic microenvironment around the drug molecules by incorporating various freely soluble acidic substances. Addition of such additives provides a dual effect of not only providing an acidic microenvironment but also imparts solubilizing effects due to the free water-soluble nature of the additives used. In the present work, Î²-cyclodextrin (Î²-CD) complexes of rofecoxib were prepared and solubilizing additives such as citric acid and ascorbic acid were incorporated in various proportions. Dissolution studies were performed in both HCl buffer (pH 1.2) and phosphate buffer (pH 7.4). The results have shown an enhanced dissolution rate of rofecoxib in both media from beta-cyclodextrin. complex, and a further enhancement of dissolution was found in presence of ascorbic acid as well as citric acid. Differential scanning calorimetery (DSC) and infrared spectroscopy (IR) spectral studies performed on the solid complexes have shown that there is no interaction of the drug with Î²-CD and the additives. Hence, Î²-CD enhances the solubility of rofecoxib, and by creating an acidic microenvironment around the drug molecules, solubility of rofecoxib can be enhanced further, which in turn will enhance the absorption of rofecoxib and produce a better pharmacological activity. Key words: acidic microenvironment, ascorbic acid, Î²-cyclodextrin, citric acid, dissolution rate, rofecoxib, solubility